2018
DOI: 10.1115/1.4039264
|View full text |Cite
|
Sign up to set email alerts
|

Embedded Two-Phase Cooling of High Flux Electronics Via Press-Fit and Bonded FEEDS Coolers

Abstract: The increasing heat densities in electronic components and focus on energy efficiency have motivated utilization of embedded two-phase cooling, which reduces system-level thermal resistance and pumping power. To achieve maximum benefit, high heat fluxes and vapor qualities should be achieved simultaneously. While many researchers have achieved heat fluxes in excess of 1 kW/cm2, vapor qualities are often below 10%, requiring a significantly large amount of energy spent on subcooling or pumping power, which mini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Numerous strategies have been employed to enhance CHF in pool boiling as well as flow boiling, such as the use of biphilic and biconductive surfaces [15], [21], [22], functionalized surfaces [23], separated liquid-vapor pathways [26], [27], microchannel flow devices [28]- [37] with sintered surfaces and varying channel cross-sections, nanowires and nanostructures [38]- [41], addition of surfactants and nanoparticles [42]- [48], increasing surface roughness and wickability [16], [25], tuning surface wettability [20], and using microporous structures [49]- [52]. Recently, Rahman et al [16] demonstrated through biotemplating of microstructures that an increase in surface roughness and wickability facilitates liquid replenishment to the surface, enhancing CHF.…”
Section: B Comparison Of Chfmentioning
confidence: 99%
“…Numerous strategies have been employed to enhance CHF in pool boiling as well as flow boiling, such as the use of biphilic and biconductive surfaces [15], [21], [22], functionalized surfaces [23], separated liquid-vapor pathways [26], [27], microchannel flow devices [28]- [37] with sintered surfaces and varying channel cross-sections, nanowires and nanostructures [38]- [41], addition of surfactants and nanoparticles [42]- [48], increasing surface roughness and wickability [16], [25], tuning surface wettability [20], and using microporous structures [49]- [52]. Recently, Rahman et al [16] demonstrated through biotemplating of microstructures that an increase in surface roughness and wickability facilitates liquid replenishment to the surface, enhancing CHF.…”
Section: B Comparison Of Chfmentioning
confidence: 99%
“…Thermal management of the switches has become a primary design goal in the packaging of power converters. Many aggressive cooling methods, such as jet cooling, spray cooling, and two-phase cooling, have been and are being developed which are capable of handling heat fluxes above 100 W/cm 2 , with some capable of dissipating near or above 1 kW/cm 2 [1][2][3][4][5]. However, such cooling methods usually involve additional complexity and lack sufficient understanding of the fundamental physics of liquid-vapor flow interaction, making accurate and reliable analysis and design optimization more difficult [6].…”
Section: Introductionmentioning
confidence: 99%
“…To improve performance over what has been reported in the literature, three major objectives are considered in this study: (1) reducing the number of layers and interfaces between the heat source and air; (2) improving the heat sink design to enable maximum heat transfer area while maintaining reasonable pressure drops; (3) creating a design with minimal footprint on board and reduced volume to enhance power density. Some of these targets, especially 2 and 3, are competing objectives.…”
Section: Introductionmentioning
confidence: 99%